Electron Scattering from Atoms, Ions and Molecules - Srivastava, Rajesh; Fursa, Dmitry V. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Electron collision physics covers a broad range of processes in atoms and molecules. Understanding these processes can be achieved via experimental and theoretical investigations that support and challenge each other. The last few decades have been witness to tremendous progress in both the computational and experimental techniques applied to study and model electron-driven processes. Access to modern supercomputer facilities has allowed for the computational modelling of collision processes involving complex atoms and molecules; in turn, this allows for a sophisticated modelling and the diagnostic assessment of various plasmas. Applications of electron collision physics range from fusion, precision measurement and attoclocks to radiation damage and biomedical research. This volume collates diverse applications of collision physics, highlighting the importance and power of theoretical and computational techniques while also presenting new experiments which disclose exciting new developments in collision processes.